Effects of a phthalate metabolite mixture on both normal and tumoral human prostate cells - Cavalca, Alexandre M. B. [UNESP]; Aquino, Ariana M. [UNESP]; Mosele, Francielle C. [UNESP]; Justulin, Luis A. [UNESP]; Delella, Flávia K. [UNESP]; Flaws, Jodi A.; Scarano, Wellerson R. [UNESP] (Wiley, 2022)
Phthalates represent a group of substances used in industry that have antiandrogenic activity and are found in different concentrations in human urine and plasma. More than 8 million tons of phthalates are used each year, predominantly as plasticizers in polyvinyl chloride (PVC) products. Phthalates are widely used in everyday consumer products and improperly discarded into the environment. Furthermore, in vivo studies carried out in our laboratory showed that a mixture of phthalates, equivalent to the mixture used in this study, deregulated the expression of genes and miRNAs associated with prostatic carcinogenic pathways. Thus, this study was designed to establish an in vitro model to assess pathways related to cell survival, proliferation, apoptosis, and biosynthesis of miRNAs, using both normal and tumoral prostatic epithelial cells exposed to an environmentally relevant mixture of phthalate metabolites. Tumor (LNCaP) and normal (PNT-2) prostatic epithelial cell lines were exposed for 24 and 72 h to vehicle control or the phthalate mixture. The selected metabolite mixture (1000 μmol/L) consisted of 36.7% monoethyl phthalate (MEP), 19.4% mono(2-ethylhexyl) phthalate (MEHP), 15.3% monobutyl phthalate (MBP), 10.2% monoisobutyl phthalate (MiBP), 10.2% monoisononyl phthalate (MiNP), and 8.2% monobenzyl phthalate (MBzP). Gene expression was performed by qRT-PCR and cell migratory potential was measured using cell migration assays. Our results showed that the mixture of phthalates increased cell turnover, oxidative stress, biosynthesis, and expression of miRNAs in LNCaP cells; thus, increasing their cellular expansive and migratory potential and modulating tumor behavior, making them possibly more aggressive. However, these effects were less pronounced in benign cells, demonstrating that, in the short term, benign cells are able to develop effective mechanisms or more resistance against the insult.
Keywords: LNCaP; miRNa; phthlate mixture; PNT2; prostate